S100 Utility of endobronchial ultrasound-guided transbronchial needle aspiration for pd-l1 testing in patients with nsclc. (15th November 2017) - Perrotta, F; Adizie, B; Maqsood, U; Elshafi, M; Jafri, S; Woolhouse, I; Munavvar, M; Evison, M; Booton, R; Baldwin, DR; Janes, SM; Bianco, A; et al.
Abstract : Rationale: Recent data have demonstrated the superiority of Pembroluzimab over chemotherapy for patients with advanced NSCLC and high (≥50% expression) of PD-L1.1 This has resulted in NICE approving Pembroluzimab as a first line treatment option for patients with advanced NSCLC in June 2017. The original trial however excluded patients with PD-L1 testing on EBUS samples. We therefore conducted a large, multicentre study to clarify whether specimens obtained by EBUS-TBNA were suitable for testing PD-L1 in patients with NSCLC. Methods: NSCLC samples acquired by EBUS-TBNA (29.4%), percutaneous biopsy (31.2%), endobronchial biopsy (13.8%), surgical (21.4%) or other techniques (4.1%) were recorded from 435 consecutive patients with known or suspected lung cancer across 5 centres in England between January 2015 and December 2016. Results: PD-L1 assessment (using the 22 C3 assay in all cases) was possible in 92.2% of patients undergoing EBUS and there was no difference in success of PD-L1 testing according to modality of tissue acquisition (p=0.18). The frequency of complications from EBUS-TBNA was similar to endobronchial or percutaneous techniques but lower than surgical procedures (5.0% vs 13.8%; p=0.03). PD-L1 expression in the cohort was high (≥50%) in 28.5%, weak (≥1%–50%) in 28.2%, whilst 43.3% of patients were PD-L1 negative. The only statistically significant predictor for PD-L1 expression in multivariate analysis was the presence of brain metastasis at diagnosis (OR 2.02; CI 1.04–3.90). 47 patients (11.4%) were treated with immunotherapy and the response rate was 16.2%. All patients that responded to immunotherapy had high (≥50%) expression of PD-L1. Conclusions: This large multicentre study demonstrates for the first time that samples obtained by EBUS-TBNA in routine practice are suitable for PD-L1 testing in patients with NSCLC. The presence of brain metastases at diagnosis predicts high PD-L1 expression in this cohort and this new finding should be tested in future clinical trials. Reference: Reck M, Rodrguez-Abreu D, Robinson AG, et al . Pembrolizumab versus Chemotherapy for PD-L1Positive NonSmall-Cell Lung Cancer. N Engl J Med 2016;375(19):1823-33. doi:10.1056/NEJMoa1606774